A checklist of ‘psocoptera’ (Psocodea) from Brazil: An update to the list of 2009 of garcía aldrete and mockford, with an identification key to the families - Aldrete, Alfonso Neri García; Silva-Neto, Alberto Moreira da (Papeis Avulsos de Zoologia, 2020)
The described species of Psocoptera currently known for Brazil are listed, with state distribution and biogeographic status. An identification key to the families recorded in Brazil is presented. © 2020, Universidade de Sao Paulo. All rights reserved.
Keywords: Geographic distribution; Neotropics; Psocids